A Study of the Quantum Correlations in a Tavis-Cummings System - Madrid Úsuga, Duvalier (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The quantum correlations of two qubits in a microcavity with dissipation and a single quantized mode of the electromagnetic field are studied. In order to study our physical system, the Tavis-Cummings model and the formalism of the master equation of the density operator under the Born-Markov approximations will be used. The cavity mode will be coupled with an external pulsed laser and the master equation of the density operator that describes the evolution of the system will be solved numerically. The concurrence, the quantum mutual information, and the quantum discord are determined for the system of two qubits. The correlations are studied as a function of the dimensionless quantity $τ = gt $ when the intensity of the laser cavity coupling varies, and two initial conditions are considered in the weak coupling regime in which the dynamic evolution of these correlations was studied.